The Effect of a nurse's home visit intervention on knowledge, dietary salt adherence, and blood pressure in hypertensive patients at primary health care - setyoadi, setyoadi; D. W., Sari; C. K., Amartasari; H., Ayuntyas; F., Akhsinadya; H., Baroya; F. F., Ferinasmara; R. G., Mufida; P. A., Azizah; A. N., Wulandari; F. I., Wati; N. I., Oktavia (University of Muhammadiyah Malang, 2024)
Introduction: Home visits are a primary health care program targeting families with chronic health problems to promote healthy behavior changes and improve the quality of life of patients. Objectives: This study aims to determine the effect of nurse home visit interventions on knowledge, dietary salt adherence, and blood pressure in hypertensive patients at the Primary Health Care (Puskesmas) in Dau District. Methods: This quantitative research uses a quasi-experimental method with a one-group pre-test post-test design. The sample consisted of 69 individuals from Kunci and Princi hamlets who suffered from hypertension. The sampling technique was purposive sampling with inclusion criteria including families with hypertension, living with family members, being able to read and write, and willing to participate as respondents. The home-visit interventions were conducted over 7 weeks and included counseling on hypertension concepts, diet, medication, physical activity, and stress management, along with ongoing monitoring during the home-visit period. Results: Statistical test results on the knowledge variable using the paired t-test showed a significance of 0.01, indicating a significant change post-intervention. The dietary salt adherence variable, assessed using the Wilcoxon rank test, showed an average increase of 24.00 from pre-intervention to post-intervention. Both systolic and diastolic blood pressure variables exhibited significant changes, with a 2-tailed significance of 0.01. Conclusions: The results of this study conclude that nurse home-visit interventions have a positive effect on knowledge, dietary salt adherence, and blood pressure in hypertensive patients.